Are your consumers variety seekers? The moderating impact on the effectiveness of free gift promotions vs. price discounts. Issue 4 (8th August 2017) - Roll, Oliver; Pfeiffer, Elenia
Abstract: The purpose of this paper is to assess the effect of consumers' variety-seeking tendency on their preference for monetary versus nonmonetary promotions (i.e. a price discount versus a free gift, respectively) and to identify possible reasons for this preference. A sample population of 150 students was surveyed. The research employed a 2 (discount/free gift) × 2 (high variety seeking/low variety seeking) between-subjects design. A two-way ANOVA was applied to analyse the effects of the promotion frame and variety seeking on perceived transaction value. The ANOVA revealed a general consumer preference for a free gift over a price discount. This outcome is moderated by the variety-seeking tendency of the consumer; that is, repetitive consumers prefer a price discount, but variety-seeking consumers favour a free gift. This study gives managers insights into the issue of what kind of price promotion is most effective under which circumstances, namely for which type of consumer segment. The practical implications of our findings recommend that if the targeted consumer segment is variety-seeking, a free gift may be optimal, yet if the target segment represents returning customers, a price discount yields better results. If no clear assignment of consumers to either segment is possible, a free gift is the preferred option.